FUNCTIONS OF MUSICAL CULTURE IN THE FORMATION OF A SPIRITUAL WORLD VIEW - Tursunova Laylo (Scholar Express Journal, 2022)
The article discusses the idea that music expresses complex social emotions, primarily moral emotions that reflect the tone of speech or weights of action in life, such as love, hate, pride, fear, aesthetic art or the subtleties of nature, glory, tragedy, humor.
Keywords: Musical Culture; Life Feeling; Mental System; Uzbek Music Performance